Ecological Assessment of the Surface Water Quality of the Guyva River - Смілий, Павло Миколайович (Київський національний університет імені Тараса Шевченка, 2020)
Method. Environmental assessment of the surface water of the Guyva River was carried out using the system of classification of standards for the assessment of surface water quality of Ukraine. On the basis of common environmental criteria, the methodology makes it possible to compare the quality of water at different sites of water bodies, in water bodies of different regions. The calculation of the ecological assessment of water quality was carried out within three blocks: block of salt composition (І1), block of trophic-saprobiological (ecological-sanitary) indicators (І2) and block of indicators of content of specific substances of toxic action (І3). The results are presented in the form of a combined environmental assessment based on the final conclusions of the three blocks and based on the calculation of the integrated environmental index (IE). Results. omprehensive studies on changing the water quality of the Guyva River were conducted within the Zhytomyr region during 2016-2017. The water quality of the river according to the final values of the integral indicators of water quality of the three blocks varies within the II and III quality classes. The total environmental indices (IEs) for the mean and worst indices are 2,9 and 3,1 respectively. In general, the water quality along the main channel of the Guyva River within the Zhytomyr region corresponds to the second class, 3 categories, 3(2) subcategories according to the average quality indicators (in the state of "good" with a slope to "very good", in terms of purity bias to "clean") and 3 subcategories by worst performance (good for good, clean enough). The total values of the integral surface water quality indicators of the Guyva River indicate their contamination by trophic-saprobiological components. Scientific novelty. For the first time, on the basis of analytical studies and stock materials, an ecological assessment of the surface waters of the Guyva River within the Zhytomyr region was carried out by three blocks of indicators: salt composition, trophic-saprobiological indicators and specific toxic substances. The integral ecological index is determined. The trends of pollutants accumulation in the surface waters of the River Guyva have been established. Practical significance. The conducted researches allowed to analyze and evaluate the ecological status of the surface waters of the Guyva River within the Zhytomyr region, which will allow to establish ecological standards of water quality and on this basis to determine the main directions for improvement of water resources and to substantiate the system of recommendations aimed at improving the ecological status of the studied basin.

Методика. Екологічну оцінку якості поверхневих вод річки Гуйва проведено із застосуванням системи класифікації нормативів оцінки якості поверхневих вод України. На основі єдиних екологічних критеріїв методика дозволяє порівняти якість води на окремих ділянках водних об’єктів, у водних об’єктах різних регіонів. Розрахунок екологічної оцінки якості води проведено в межах трьох блоків: блоку сольового складу (І1), блоку трофо сапробіологічних (еколого-санітарних) показників (І2) та блоку показників вмісту специфічних речовин токсичної дії (І3). Результати подаються у вигляді об’єднаної екологічної оцінки, яка ґрунтується на заключних висновках по трьох блоках та полягає в обчисленні інтегрального екологічного індексу (ІЕ). Результати. Комплексні дослідження, щодо зміни якості води річки Гуйва проводилися у межах Житомирської області впродовж 2016-2017 років. Якість води річки за підсумковими значеннями інтегральних показників якості води трьох блоків варіюються в межах ІІ і ІІІ класів якості. Підсумкові екологічні індекси (ІЕ) для середніх і найгірших значень індексів становлять 2,9 і 3,1 відповідно. Загалом якість води за основним руслом рычки Гуйва в межах Житомирської області відповідає ІІ класу, 3 категорії, 3(2) субкатегорії за середніми показниками якості (за станом «добрі» з ухилом до «дуже добрих», за ступенем чистоти «досить чисті» з ухилом до «чистих») та 3 субкатегорії за найгіршими показниками (за станом «добрі», за ступенем чистоти «досить чисті»). Підсумкові величини інтегральних показників якості поверхневих вод річки Гуйва свідчить про їх забруднення за трофо-сапробіологічними компонентами. Наукова новизна. Вперше на основі аналітичних досліджень та фондових матеріалів проведена екологічна оцінка поверхневих вод річки Гуйва в межах Житомирської області за трьома блоками показників: сольового складу, трофо-сапробіологічних показників та специфічних речовин токсичної дії. Визначено інтегральний екологічний індекс. Встановлені тенденції накопичення забруднюючих речовин у поверхневих водах річки Гуйва. Практична значимість. Виконані дослідження дозволили проаналізувати та оцінити екологічний стан поверхневих вод річки Гуйва в межах Житомирської області, що дозволить встановити екологічні нормативи якості води та на їх основі визначити основні напрямки щодо поліпшення стану водних ресурсів і обґрунтувати систему рекомендацій спрямованих на покращення екологічного стану досліджуваного басейну в межах області.
Екологічна оцінка якості поверхневих вод річки Гуйва
Keywords: поверхневі води; річка; басейн річки; екологічна оцінка; якість води; поверхностные воды; река; бассейн реки; экологическая оценка; качество воды; surface water; river; river basin; environmental assessment; water quality